Analysis of isolated phase windings and permanent magnet assists high energy efficient hybrid‐reluctance motor for electric vehicle - Sundaramoorthy Prabhu; Arun Vijayakumar; Albert Alexander Stonier; Geno Peter; Sonam Dorji; Vivekananda Ganji (IET Electrical Systems in Transportation, 2023)
Abstract This article describes the electromagnetic analysis of high efficient hybrid motor, which comprises the salient features of switched reluctance motor (SRM) and spoke‐type brushless DC motor. The main objective is to develop a motor with a high‐power density and winding faulty capability. Furthermore, this research article extends in the manner to increase the power density of the motor through the sensitivity analysis on rotor geometry by replacing the rotating part of SRM and adopting the rotor of spoke type brushless DC motor, originating the hybrid motor with the high‐power density and enhanced efficiency. To ensure the winding fault capability, a SRM‐based stator winding is adopted. Then, the modelling process for hybrid motor 48 V, 1500 RPM, 2 kW, and 12.7 Nm are detail in both analytical and finite element methods. The electromagnetic analysis is carried out to estimate the torque characteristics and flux pattern of the proposed motor. Furthermore, the proposed motor is analysed with the selection of laminating core material among M 27 24 Ga, 36F155, 46F165, 47F165, M 420 50D, and arnon 7. This infers 36F155 material assists proposed motor has high‐performance characteristics. The vibration frequencies are investigated in modal aspects to estimate the natural frequencies of vibrations. These analyses are validated among analytical and finite element results under no‐load conditions.